Моделирование фотопреобразователя с учетом спектральной зависимости коэффициента поглощения - Натарова, Ю. В.; Галат, А. Б. (ХНУРЕ, 2017)
The production of energy from traditional sources has a disastrous effect on the ecological state of the planet. In this work we study a model of a photoconverter, which is a multilayer structure with interlayer transitions. The light absorption efficiency of a-Si: H / c-Si heterojunction, used in a solar cell, investigated in this work. In a report of the results of calculations of the basic parameters of solar cells by means of analytical models are presented. The calculations take into account the spectrum of sunlight AM1.5, the dependence of the conversion rate and absorption coefficients from light quantum energy.
Keywords: Моделирование фотопреобразователя; Коэффициент поглощения